2015
DOI: 10.1002/app.41850
|View full text |Cite
|
Sign up to set email alerts
|

Poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) films for food packaging: Physical–chemical and structural stability under food contact conditions

Abstract: The objective of the present article is to bring new insights into the relationships between the structural and physical-chemical stability and the inertness of PHBV films with respect to the targeted food packaging application. It is concluded from overall migration tests that PHBV films can be used as food contact materials for any type of food. Functional properties of PHBV films (mechanical properties and water vapor permeability) were also very stable after contact at 40°C during 10 days with all food sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 24 publications
3
17
0
2
Order By: Relevance
“…These results reflect the plasticizing effect on the film that could be due to the sorption and diffusion of the solvent within the bionanocomposite structure. Such phenomenon was observed for the bioplastic film based on poly(3-hydroxybutyrate- co-3-hydroxyvalerate) (Chea, Angellier-Coussy, Peyron, Kemmer, & Gontard, 2016).…”
Section: Kinetic Releasementioning
confidence: 53%
“…These results reflect the plasticizing effect on the film that could be due to the sorption and diffusion of the solvent within the bionanocomposite structure. Such phenomenon was observed for the bioplastic film based on poly(3-hydroxybutyrate- co-3-hydroxyvalerate) (Chea, Angellier-Coussy, Peyron, Kemmer, & Gontard, 2016).…”
Section: Kinetic Releasementioning
confidence: 53%
“…Substances arising from physical–chemical material degradation as well as breakdown products and/or intentionally added additives could migrate during the contact of the materials with the food. A work has been recently published to highlight the relationships between the structural and physical–chemical stability and the inertness of PHBV films with respect to the targeted food packaging application . It was concluded that the functional properties of PHBV films (mechanical properties and water vapor permeability) were very stable after contact at 40°C during 10 days with all food simulating liquids tested (water, acetic acid 3% (w/v), ethanol 20% (v/v)m and iso‐octane), except with ethanol 95% (v/v), which was also identified as the worst case in terms of overall migration.…”
Section: Understanding and Controlling Mass Transfer Properties Of Bimentioning
confidence: 98%
“…In the framework of the European program EcoBioCap (http://www.ecobiocap.eu), a huge effort was put on the development and characterization of biocomposites made of poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) and ligno‐cellulosic fiber for food packaging applications. Several papers of our group focusing on mechanical properties and aging in real conditions of use, have highlighted the role of water transfer within the material, which would be determinant for its stability. Therefore, the present study aims at deciphering water vapor transfer mechanisms in these biocomposites (PHBV/wheat straw fibers).…”
Section: Introductionmentioning
confidence: 99%